Chronic Alcohol Exposure Induces Aberrant Mitochondrial Morphology and Inhibits Respiratory Capacity in the Medial Prefrontal Cortex of Mice - Shang, Pei; Lindberg, Daniel; Starski, Phillip; Peyton, Lee; Hong, Sa-Ik; Choi, Sun; Choi, Doo-Sup (Frontiers in Neuroscience, 2020)
Alcohol use disorder (AUD) is characterized as chronic, relapsing disease evolving a pattern of excessive drinking despite the negative consequences to an individual’s life. Severe chronic alcohol use impairs the function of the medial prefrontal cortex (mPFC), which is attributed to the alcohol-induced cognitive and executive dysfunction. However, how alcohol deteriorates the brain mitochondria, especially in the mPFC, which is critically involved in cognitive and executive function, has not been clearly understood. Here, we identified morphological and functional changes in mitochondria in the mPFC in C57BL6/J mice after 8 hours of withdrawal from chronic intermittent alcohol (CIA) exposure. Three-dimensional serial block-face scanning electron microscopy (SBFSEM) reconstruction revealed that CIA exposure disrupted mitochondria morphology and formed mitochondria-on-a-string (MOAS). Furthermore, alcohol significantly affected mitochondrial bioenergetics measured by a Seahorse Extracellular Flux Analyzer. We also elucidated decreased expression of fusion (mitofusin 2, Mfn2) and increased fission (mitochondrial fission 1 protein, Fis1) protein in the mPFC from alcohol-treated mice. Taken together, our study suggests that CIA exposure impairs mitochondrial dynamics and function in the mPFC.